Hypoglycemic Activity of Aqueous Extract of Latex from Hancornia speciosa Gomes: A Study in Zebrafish and In Silico - Rosana Tomazi; Ângela Costa Figueira; Adriana Maciel Ferreira; Diego Quaresma Ferreira; Gisele Custódio de Souza; Wandson Braamcamp de Souza Pinheiro; José Rodrigues Pinheiro Neto; Geilson Alcantara da Silva; Henrique Barros de Lima; Lorane Izabel da Silva Hage-Melim; Arlindo César Matias Pereira; José Carlos Tavares Carvalho; et al. (MDPI AG, 2021)
Hancornia speciosa Gomes is a tree native to Brazil and has therapeutic potential for several diseases. Ethnopharmacological surveys have reported that the plant is used as a hypoglycemic agent and to lose weight. This study aimed to evaluate the effects of the aqueous extract from H. speciosa latex (LxHs) in a zebrafish model of diabetes. The extract was evaluated through high-performance thin-layer chromatography (HTPLC), nuclear magnetic resonance (NMR), and Fourier-transform infrared spectroscopy (FT-IR). We then tested treatments with LxHs (500, 1000, and 1500 mg/kg) by assessing blood glucose levels in alloxan-induced diabetic animals, and metformin was used as a control. The toxicity was evaluated through histopathology of the pancreas and biochemical assessment of serum levels of AST, ALT, creatinine, and urea. The extract was also assessed for acute toxicity through several parameters in embryos and adult animals. Finally, we performed in silico analysis through the SEA server and docking using the software GOLD. The phytochemical study showed the compounds cornoside, dihydrocornoide, and 1-O-methyl-myoinositol (bornesitol). The treatment with all doses of LxHs significantly decreased alloxan-induced hyperglycemia without any significant histological or biochemical abnormalities. No significant frequency of teratogenesis was observed in the embryos exposed to the extract, and no significant behavioral changes or deaths were observed in adult animals. In silico, the results showed a potential interaction between inositol and enzymes involved in carbohydrates' metabolism. Overall, the results show a hypoglycemic activity of the extract in vivo, with no apparent toxicity. The computational studies suggest this could be at least partially due to the presence of bornesitol, since inositols can interact with carbohydrates' enzymes.